PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN EMPATI SISWA KELAS XI SMK FARMASI IKASARI PEKANBARU TP. 2014/2015 - Ayu Apriliani; Rosmawati '; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study Aimed to see if there was an effect of group counseling tothe increase of student empathy. The sample was a class XI student of SMK FARMASIIKASARI PEKANBARU who have low empathy numbered 30 people. In this study therewere five times treatment group roomates guidance begins with a questionnaire pretestand posttest questionnaire terminated. Reviews These results indicate that an increaseof students in empathy after the implementation of the guidance group contributions asmuch as 36.8%.Keywords: Empathy, Guidance Group